General practice registrars' clinical exposure to dermatological procedures during general practice training: a cross-sectional analysis. Issue 6 (2nd November 2018) - Tng, Er Tsing Vivian; Tapley, Amanda; Davey, Andrew; De Zwaan, Sally; Morgan, Simon; van Driel, Mieke; Holliday, Elizabeth; Ball, Jean; Catzikiris, Nigel; Henderson, Kim; Mulquiney, Katie; Spike, Neil; et al.
ABSTRACT: Australian general practitioners (GPs) commonly manage dermatological conditions requiring procedures. GP registrars have limited pre-vocational training exposure to dermatology and find skin problems challenging. We aimed to establish the prevalence, nature and associations of GP registrars' performance of skin procedures. We conducted a cross-sectional analysis from the Registrar Clinical Encounters in Training cohort study. Multivariable logistic regression was used to establish associations of our outcome (skin procedures, both including and excluding cryotherapy). Independent variables included patient and doctor demographics, diagnoses/problems managed and registrars' recourse to in-consultation assistance/information. A total of 1161 registrars provided data on 166, 988 consultations, recording 2927 skin procedures (16.7% of all procedures; performed in 1.7% of consultations). Cryotherapy, excision, punch biopsy and shave biopsy were most common. More complex procedures were performed infrequently. Significant associations of performing procedures included rural/remote location (compared to major city), male patients, patient age 65+ (compared to age 15–34) and registrars seeking in-consultation information/assistance. Skin procedures were less likely for Aboriginal patients or those from non-English-speaking backgrounds. For non-cryotherapy procedures, rurality was not significantly associated, but significant differences were found between training regions. In summary, GP registrars perform fewer dermatological procedures compared to established GPs. Findings will inform GP vocational training in skin procedures.